Damma One of the Villages of Anbar - Al-Hadithy, Anmar Nazar Abdulateef (Al-Adab Journal, 2021)
The study of villages and cities in the historical field indicated an important role for several reasons, including the lack of news about them and the extinction of our information about them. Including showing the role that these villages contributed to in historical, economic, military and even social events, if any. The village of Damma has a distinct share of such a role. Despite the scarcity of information and historical references about this village in its ancient history before Islam, it formed an image, albeit partial, of the role that this village played in historical events in order for this role to expand from the information that we received about it in Islamic history, to form a clearer picture of its prominent role and the value it gained from this role. Such a study enriches historical knowledge and highlights the roles of villages and cities, no matter how small their area is, but it imprinted their imprint in the cognitive memory and preserved for us a distinct heritage that was the fulcrum of these villages in the history of the Arabs before Islam and continued afterwards to exercise their historical role in it.